2021
DOI: 10.1371/journal.ppat.1009168
|View full text |Cite
|
Sign up to set email alerts
|

Carbomer-based adjuvant elicits CD8 T-cell immunity by inducing a distinct metabolic state in cross-presenting dendritic cells

Abstract: There is a critical need for adjuvants that can safely elicit potent and durable T cell-based immunity to intracellular pathogens. Here, we report that parenteral vaccination with a carbomer-based adjuvant, Adjuplex (ADJ), stimulated robust CD8 T-cell responses to subunit antigens and afforded effective immunity against respiratory challenge with a virus and a systemic intracellular bacterial infection. Studies to understand the metabolic and molecular basis for ADJ’s effect on antigen cross-presentation by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Unlike T RM -centric protection against IAV, either mucosal or parenteral vaccinations protect against the β-variant of SARS-CoV-2, which suggest that both T RM s and systemic migratory memory T cells can protect against SARS-CoV-2. Likewise, systemic migratory T cell memory controls mucosal challenge with vaccinia virus ( 40 ). Taken together, these findings highlight the differences in tenets of T cell–dependent protective immunity to respiratory infections with viruses, such as influenza virus, SARS-CoV-2, and poxvirus, and demonstrate the relative importance of antibodies and T cells in immune prophylaxis against SARS-CoV-2 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike T RM -centric protection against IAV, either mucosal or parenteral vaccinations protect against the β-variant of SARS-CoV-2, which suggest that both T RM s and systemic migratory memory T cells can protect against SARS-CoV-2. Likewise, systemic migratory T cell memory controls mucosal challenge with vaccinia virus ( 40 ). Taken together, these findings highlight the differences in tenets of T cell–dependent protective immunity to respiratory infections with viruses, such as influenza virus, SARS-CoV-2, and poxvirus, and demonstrate the relative importance of antibodies and T cells in immune prophylaxis against SARS-CoV-2 variants.…”
Section: Discussionmentioning
confidence: 99%
“…For lipidomics, raw data files were processed using Compound Discoverer 2.1 (Thermo Scientific) and Lipidex . The parameters were mainly adapted from previous literature. Lipid retention time range was set to 60.1–89.0 min (0.5 min tolerance) and the precursor mass range was set to 100–5000 Da (10 ppm mass tolerance) for aggregation of chromatographic peaks into distinct compound groups. Peak detection required a signal-to-noise ratio of 1.5, a minimum peak intensity of 5 × 10 5 , and a maximum peak width of 0.75 min.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, subcutaneous and intranasal vaccination generated systemic and mucosal T cell memory respectively, but only mucosal T cell memory elicited by intranasal vaccination protected against influenza virus. Other studies from our group demonstrated that ADJ robustly stimulates systemic antigen-specific CD4 and CD8 T-cell responses to subunit protein antigen, and protected against vaccinia virus, Listeria monocytogenes (L. monocytogenes ) and respiratory fungal infections ( 221 , 223 , 234 ). Specifically, upon subcutaneous vaccination of mice, ADJ elicited effector CD8 T cells that differentiated into a distinct subset of granzyme B-expressing CD27 LO ‘effector-like’ memory CD8 T cells, which provided highly effective immunity to intracellular bacteria L. monocytogenes in spleen and liver ( 222 ).…”
Section: Adjuvants and Cross-presentationmentioning
confidence: 89%